Pulmonary Neuroendocrine Neoplasms Overexpressing Epithelial-Mesenchymal Transition Mechanical Barriers Genes Lack Immune-Suppressive Response and Present an Increased Risk of Metastasis - Prieto, Tabatha Gutierrez; Baldavira, Camila Machado; Machado-Rugolo, Juliana; Farhat, Cecília; Olivieri, Eloisa Helena Ribeiro; de Sá, Vanessa Karen; da Silva, Eduardo Caetano Abilio; Balancin, Marcelo Luiz; Ab´Saber, Alexandre Muxfeldt; Takagaki, Teresa Yae; Cordeiro de Lima, Vladmir Cláudio; Capelozzi, Vera Luiza (Frontiers in Oncology, 2021)
Typical carcinoids (TC), atypical carcinoids (AC), large cell neuroendocrine carcinomas (LCNEC), and small cell lung carcinomas (SCLC) encompass a bimodal spectrum of metastatic tumors with morphological, histological and histogenesis differences, The hierarchical structure reveals high cohesiveness between neoplastic cells by mechanical desmosomes barrier assembly in carcinoid tumors and LCNEC, while SCLC does not present an organoid arrangement in morphology, the neoplastic cells are less cohesive. However, the molecular mechanisms that lead to PNENs metastasis remain largely unknown and require further study. In this work, epithelial to mesenchymal transition (EMT) transcription factors were evaluated using a set of twenty-four patients with surgically resected PNENs, including carcinomas. Twelve EMT transcription factors (BMP1, BMP7, CALD1, CDH1, COL3A1, COL5A2, EGFR, ERBB3, PLEK2, SNAI2, STEAP1, and TCF4) proved to be highly expressed among carcinomas and downregulated in carcinoid tumors, whereas upregulation of BMP1, CDH2, KRT14 and downregulation of CAV2, DSC2, IL1RN occurred in both histological subtypes. These EMT transcription factors identified were involved in proliferative signals, epithelium desmosomes assembly, and cell motility sequential steps that support PNENs invasion and metastasis in localized surgically resected primary tumor. We used a two-stage design where we first examined the candidate EMT transcription factors using a whole-genome screen, and subsequently, confirmed EMT-like changes by transmission electron microscopy and then, the EMT-related genes that were differentially expressed among PNENs subtypes were predicted through a Metascape analysis by in silico approach. A high expression of these EMT transcription factors was significantly associated with lymph node and distant metastasis. The sequential steps for invasion and metastasis were completed by an inverse association between functional barrier created by PD-L1 immunosuppressive molecule and EMT transcriptional factors. Our study implicates upregulation of EMT transcription factors to high proliferation rates, mechanical molecular barriers disassembly and increased cancer cell motility, as a critical molecular event leading to metastasis risk in PNENs thus emerging as a promising tool to select and customize therapy.